Utilization of Wordwall Gamification Application to Improve Students' Cognitive Creativity and Critical Thinking in English Lessons - Rais Abin; Sultan; La Ode Muhammad Idrus Hamid B.; Ray Suryadi; Kevin Hendrawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
In the digital era, interactive learning aligned with Generation Z's characteristics is crucial. Based on constructivist theory, gamification through Wordwall offers innovative ways to enhance student engagement, creativity, and critical thinking. Yet, English instruction for eighth-grade students at SMP Negeri 2 Samaturu remains traditional, limiting cognitive creativity and critical thinking development. This research analyzes Wordwall's impact on these skills among 25 randomly selected eighth-grade students. A quantitative pre-experimental one-group pretest-posttest design was implemented over eight weeks (three sessions weekly). Instruments included writing tests for cognitive creativity, speaking tests for critical thinking, and observation checklists for engagement. SPSS one-sample t-test analysis showed significant gains. Cognitive creativity reached a mean of 80.12 (t=5.28 > t-table 2.06, p<0.05, Cohen's d=1.06—large effect). Critical thinking averaged 81.64 (t=6.18 > 2.06, p<0.05, d=1.24—large effect), confirming Wordwall's substantial influence. The intervention fostered 21st-century skills effectively. Limitations encompass the pre-experimental design and small single-school sample. Recommendations urge Wordwall integration in junior high curricula; future studies should adopt randomized controlled trials with larger, diverse cohorts. Keywords: Wordwall, gamification, cognitive creativity, critical thinking, English learning.